The Antecedent of Customer Satisfaction towards to Attitudinal Loyalty and Behavioural Loyalty (Study at Customers of PT. Telkom Indonesia Witel Denpasar) - Kardiyasa, Komang Agus Putra; Hartati, Rukmi Sari; Dipayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2023)
Telkom Indonesia introduced fixed broadband, with its IndiHome product in 2015. According to the Triple Play service, IndiHome's flagship service, as well as other services, the core of IndiHome products is its internet service. Other services, such as voice (telephone) and interactive television (UseeTV) are ride products (augmented products). The goal of this study is to provide insight for future studies that will be conducted by researchers on service quality, which includes network quality, customer service, information quality, and customer data security. It also involves customer satisfaction, behavioural loyalty, and attitude loyalty. The issue in this study is that the number of customers who churn (unsubscribe the services) is increasing, indicating that customers are less loyal to IndiHome services. This study sent a questionnaire to 258 Witel Denpasar respondents who had subscribed to IndiHome for more than one month and had visited the Plaza Telkom in August 2022 in order to collect respondents' responses. The sampling technique used in this research is purposive sampling, which is a sampling technique with certain considerations. Data collection in this study was carried out by distributing questionnaires online via the Google form. And the data analysis technique used in this study is the structural equation modelling (SEM) method using LISREL 8.8 software. Keywords: Customer Satisfaction; IndiHome; Structural Equation Model; Behavioural Loyalty